Intramuscular Reactivity of the Modified Graphene Oxides and Their Bio-Reactivity in Aging Muscle - Xiaoting Jian; Jiayin Wang; Jijie Hu; Yangyang Li; Qisen Wang; Han Wang; Jingwen Huang; Yu Ke; Hua Liao (Journal of Functional Biomaterials)
To enhance the biocompatibility and drug delivery efficiency of graphene oxide (GO), poly(ethylene glycol) (PEG), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), or its triblock copolymer PEG-PHBV-PEG (PPP) were used to chemically modify GO. However, it is still unknown whether non-toxic polymer-modified GO mediates muscle toxicity or triggers intramuscular inflammation. This study aims to investigate the biological reactivity and inflammation/immune response induced by PEG, PHBV, or PPP modified GO when injected into the tibialis anterior (TA) muscle of mice prior to drug loading. The results showed that after muscle exposure, the coating of biocompatible polymers on GO is more likely to provoke muscle necrosis. Muscle regeneration was found to occur earlier and more effectively in muscle treated with hydrophilic PEG-GO and PPP-GO compared to muscle treated with hydrophobic PHBV-GO. When observing the transient muscle macrophage invasion of three modified GOs, PHBV-GO caused severe muscle necrosis in the early stage, induced a delayed peak of macrophage aggregation, and caused severe inflammatory progression. All three kinds of modified GO induced T cell aggregation to varying degrees, but PEG-GO induced early mass muscle recruitment of CD4+ T cells and was more sensitive to cytotoxic T cells. Based on the higher biocompatibility of PPP-GO in muscles, PPP-GO was implanted into the muscles of old or adult mice. Compared to adult mice, aged mice are more vulnerable to the stress from PPP-GO, as demonstrated by a delayed inflammatory response and muscle regeneration.